2023
DOI: 10.1002/smll.202204293
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Route of Systemic Delivery Control the In Vivo Dynamics and Breakdown of Radiolabeled Gold Nanostars

Abstract: The in vivo dynamics of nanoparticles requires a mechanistic understanding of multiple factors. Here, for the first time, the surprising breakdown of functionalized gold nanostars (F‐AuNSs) conjugated with antibodies and 64Cu radiolabels in vivo and in artificial lysosomal fluid ex vivo, is shown. The short‐term biodistribution of F‐AuNSs is driven by the route of systemic delivery (intravenous vs intraperitoneal) and long‐term fate is controlled by the tissue type in vivo. In vitro studies including endocytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Such immunoglobulin enrichment in the MS- and HS-derived PC might reflect the relative abundance of these molecules in the whole serum. Indeed, immunoglobulins are among the most abundant proteins in the PC deposited on NPs incubated in full HS, such as SiO 2 NPs; COOH-, NH 2 -, and −CH 3 -surface-modified SiO 2 NPs; gold NPs; , and polystyrene (PS) NPs . The enrichment of immunoglobulins in MS- and HS-derived PCs may facilitate and modulate their uptake by cells through Fc receptors and cell activation .…”
Section: Resultsmentioning
confidence: 99%
“…Such immunoglobulin enrichment in the MS- and HS-derived PC might reflect the relative abundance of these molecules in the whole serum. Indeed, immunoglobulins are among the most abundant proteins in the PC deposited on NPs incubated in full HS, such as SiO 2 NPs; COOH-, NH 2 -, and −CH 3 -surface-modified SiO 2 NPs; gold NPs; , and polystyrene (PS) NPs . The enrichment of immunoglobulins in MS- and HS-derived PCs may facilitate and modulate their uptake by cells through Fc receptors and cell activation .…”
Section: Resultsmentioning
confidence: 99%
“…(i) Whereas gold NPs has been extensively used for SERS in vivo due to their biocompatibility, solid metal NPs typically accumulate in organs of the reticuloendothelial system (liver and spleen) and have very slow breakdown and clearance in vivo . This has been supported by several findings including our group’s recent work. (ii) Metal NPs are known to aggregate easily, and several surface protective ligands are necessary to enable colloidal stability . While high molecular weight ligands such as PEG are excellent in coating the surface and providing NP stability, they also compromise SERS signal of Raman reporters.…”
Section: Metal-free Nanoprobes For Applications In Biological Raman-s...mentioning
confidence: 62%
“…It has been found that USIONPs is mainly eliminated by phagocytosis of macrophages in vivo within 24–72 h. , The physicochemical properties of the nanomaterial themselves have been reported to affect the elimination mechanisms and results of macrophages, that is, chemical compositions, size, morphology and surface modification. Consequently, there are many unclear and doubtable cognitions about the fate of IONPs after being phagocytized. For example, the subcellular distribution, intracellular transport and metabolism, and exocytosis of USIONPs are still unclear, but these obscure questions have been reported to determine the efficacy and safety of large-sized IONPs in vitro and in vivo . With the development of precision medicine, the dynamically quantitative study of the intracellular distribution of IONPs has become inevitable and ignorable. Unfortunately, the analysis of intracellular transport pathways and their flux are rarely reported, which seriously limits the optimal design, function exertion, and application of IONPs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the subcellular distribution, intracellular transport and metabolism, and exocytosis of USIONPs are still unclear, but these obscure questions have been reported to determine the efficacy and safety of large-sized IONPs in vitro and in vivo . 23 25 With the development of precision medicine, the dynamically quantitative study of the intracellular distribution of IONPs has become inevitable and ignorable. Unfortunately, the analysis of intracellular transport pathways and their flux are rarely reported, which seriously limits the optimal design, function exertion, and application of IONPs.…”
Section: Introductionmentioning
confidence: 99%